2022
DOI: 10.1177/09544070211072665
|View full text |Cite
|
Sign up to set email alerts
|

Improved NSGA-II to solve a novel multi-objective task allocation problem with collaborative tasks

Abstract: From the perspective of practical application, a novel task allocation problem for multi-vehicle systems is proposed. The goal is to allocate an optimal route for each vehicle to execute tasks. The planning result is a comprehensive decision considering the influence of time windows, collaborative tasks, and recharging. This problem is represented as a new extension of the classical vehicle routing problem and a multi-objective integer programming mathematical model is established. The objective functions are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…However, as the problem scale increases, the difficulty of solving this type of algorithm increases, and heuristic algorithms become the best choice. The previous research revealed that NSGA-II has the advantages of simple structure and high searchability, and it is widely used to solve the VRP (41). With regard to algorithm selection, NSGA-II was selected.…”
Section: Solution Methodsmentioning
confidence: 99%
“…However, as the problem scale increases, the difficulty of solving this type of algorithm increases, and heuristic algorithms become the best choice. The previous research revealed that NSGA-II has the advantages of simple structure and high searchability, and it is widely used to solve the VRP (41). With regard to algorithm selection, NSGA-II was selected.…”
Section: Solution Methodsmentioning
confidence: 99%
“…The benchmark function was the test tool and the suspension system was the simulation environment. The results showed that the algorithm had good applicability and potential in parameter optimization [17].…”
Section: Related Workmentioning
confidence: 95%